The Third String : Odd Craft, Part 12. - Jacobs, W. W. (William Wymark), 1863-1943; Owen, Will, 1869-1957 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Third String" by W. W. Jacobs is a comedic novella that falls into the genre of humorous fiction, likely written in the early 20th century. The narrative centers around the farcical dealings of sailors and their escapades on shore, particularly focusing on themes of love and rivalry. Through the lens of humor, the book explores the often tumultuous relationship between men and women, and the follies that arise from romantic pursuits. The story follows Ginger Dick, a sailor who falls hopelessly in love with Miss Tucker, a barmaid at the Jolly Pilots pub. Ginger's infatuation leads him to fabricate a backstory as a prize-fighter to impress her, ultimately culminating in a comically mismatched boxing match against Bill Lumm, a real prize-fighter with a reputation for violence. With the encouragement of his friends and a desire to vindicate himself, Ginger enters the fight, gaining unexpected fame when he wins. However, the twist comes when he discovers that the fight was staged to ensure he would win the affections of Miss Tucker, setting up a humorous and ironic conclusion as he learns of evolving relationships and the complex social dynamics at play. (This is an automatically generated summary.)
Release date is 2004-04-01
Produced by David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; Sailors -- Fiction